ChemInform Abstract: Pd/C‐Mediated Depropargylation of Propargyl Ethers/Amines in Water. Issue 23 (16th May 2013) - Rambabu, D.; Bhavani, S.; Swamy, Nalivela Kumara; Rao, M. V. Basaveswara; Pal, Manojit
Abstract A simple and inexpensive method is presented for the regioselective cleavage of (het)aryl propargyl ethers and amines as an important step in natural product synthesis.